Equal Effects of Low- and Moderate-Volume Supplementary Plyometric Training on Sprint, Change of Direction Ability, and Lower-Limb Power in Preadolescent Female Handball Players - Konstantinos S. Noutsos; Panagiotis G. Meletakos; Magdalini Kepesidou; Gregory C. Bogdanis (Journal of Functional Morphology and Kinesiology)
Background: This study compared the effects of low- and moderate-volume supplementary plyometric training in preadolescent female handball players. Methods: Thirty-nine preadolescent handball players (age: 12.9 ± 0.5 years, maturity offset: −1.50 ± 0.56 years) were randomly assigned into three groups: low-volume plyometric training group (LPT, n = 12); moderate-volume plyometric training group (MPT, n = 15); and control group (CG, n = 12). The supplementary plyometric training program was performed twice per week for 10 weeks, along with normal training (3 times/week). Each supplementary session included two upper- and three lower-body exercises performed for two sets (LPT, 36–54 foot contacts, duration 12 min) or four sets (MPT, 72–108 foot contacts, duration 24 min). The CG performed technical handball drills for 20 min. Results: Compared with the control group, both LPT and MPT resulted in similar improvements in modified T-test performance (15.1% and 18.6%, p < 0.01, respectively); linear sprint performance over 5, 10, and 20 m (between 5.1% and 8.8%, p = 0.02 to 0.001); countermovement jump (28.0% and 22.1%, p < 0.05, respectively); and standing long jump (12.6% and 12.5%, p = 0.024, respectively). Handgrip strength and overarm shot ball velocity improved similarly in all groups (CG, MPT, and LPT), by 8–11% (p < 0.01). Conclusions: Very-low-volume supplementary plyometric training performed for 12 min per session for two sessions per week results in considerable improvements in running speed, change of direction ability, and leg power and is as effective as a moderate-volume program. These findings are important for pre-adolescent female team sports players, who may benefit from a minimal but effective supplementary training, resulting in large benefits in leg speed and power.